Disconnection between sugars reduction and calorie reduction in baked goods and breakfast cereals with sugars-related nutrient content claims in the Canadian marketplace - Wang, Ye Flora; Marsden, Sandra; DiAngelo, Chiara; Clarke, Abigail; Chung, Anita; Yu, Jessica; Fan, Zhongqi; Cooper, Julian; Kitts, David (Frontiers in Nutrition, 2025)
IntroductionNutrition claims aim to highlight key attributes in foods and assist consumers to make informed dietary choices. Consumers generally perceive products with claims related to lower sugars content as being healthier. Food manufacturers also use these claims to highlight reformulation action in response to consumer demands and government policies.MethodsA cross-sectional analysis of baked goods and breakfast cereals in the Canadian marketplace was conducted, focusing on the use of sugars-related nutrient content claims (i.e., “no added sugars,” “lower/reduced in sugars,” “sugar-free”) and changes in nutrients and energy content in reformulation strategies. Baked goods and breakfast cereals with sugars-related claims in Canada as of December 2022 were obtained from the Mintel Global New Products Database. Current product availability was verified using websites from manufacturers and major food retailers. Corresponding reference products were identified based on claim criteria specified by the Canadian Food Inspection Agency. Differences in energy, macronutrient content and key ingredients involved in sugars reformulation were assessed between claim and reference products.ResultsA total of 111 baked goods and 23 breakfast cereal products were included. No significant difference was found in mean energy content between the claim and reference products for all subcategories, except for “unsweetened” baked goods, where the energy content in claim products was significantly higher than that of the reference products (p < 0.001). Specifically, 49% of products with claims of “no added sugar,” 27% of “sugar-free,” and 23% of “lower/reduced in sugar” had higher energy content compared to corresponding reference products. Sugar alcohols, dietary fibers, non-nutritive sweeteners and starch were the top ingredients used in place of added sugars in claim products.ConclusionNo significant difference in mean total energy content (per 100 g) between baked goods and breakfast cereals carrying sugars-related claims was found, despite various sugar reduction strategies. Thus, these claims could be misleading to consumers who expect such products to be lower in total calories. Food manufacturers are encouraged to reformulate products with improved calorie and nutrition profiles rather than using a single-nutrient focus. Consumers education on these issues can help them be mindful of the presence and unintended consequences of common sugar-replacement practices.